Design Of Web-Based Online Booking Application For Motor Vehicle Repair Using Codeigniter Framework - Anisa, Tasya Nurul; Riswaya, Asep Ririh; Oktavia, Oktavia; Tay, En (Informatics Management, Engineering and Information System Journal, 2025)
This study presents the development and testing of an IoT-based temperature and humidity management system designed for mushroom cultivation. The system effectively utilizes a DHT sensor and a scheduling mechanism to monitor and control environmental conditions. Key findings reveal that the IoT-based control system allows mushroom farmers to access real-time data through a user-friendly web interface and control unit, facilitating immediate adjustments to optimize growth conditions. Testing confirmed the system's capability to maintain essential temperature and humidity levels: 22–28°C and 80–90% during mycelium development and 16–25°C and 90–95% during the fruiting body stage. These controlled conditions significantly enhance mushroom growth and productivity compared to traditional cultivation methods. The implementation of this IoT-based system not only improves the quality and yield of mushroom production but also increases operational efficiency for farmers. By integrating modern technology into agricultural practices, this study demonstrates the potential of IoT to transform conventional farming approaches into more effective and sustainable operations.